Inhibitor of Apoptosis Proteins in Pediatric Leukemia: Molecular Pathways and Novel Approaches to Therapy - Fulda, Simone (Frontiers in Oncology, 2014)
Inhibitor of Apoptosis (IAP) proteins are a family of proteins with antiapoptotic functions that contribute to the evasion of apoptosis, a form of programmed cell death. IAP proteins are expressed at high levels in a variety of human cancers including childhood acute leukemia. This elevated expression has been associated with unfavorable prognosis and poor outcome. Therefore, IAP proteins are currently exploited as therapeutic targets for cancer drug discovery. Consequently, small-molecule inhibitors or antisense oligonucleotides directed against IAP proteins have been developed over the last years. Indeed, IAP antagonists proved to exhibit in vitro and in vivo antitumor activities against childhood pediatric leukemia in several preclinical studies. Thus, targeting IAP proteins represents a promising molecular targeted strategy to overcome apoptosis resistance in childhood leukemia which warrants further exploitation.